Preparation method of anti-shrinkage polypropylene material

By adding low shrinkage modifiers, tougheners and modified whiskers to the polypropylene material to hinder their crystallization and formation of a skeleton, the problem of high shrinkage rate of polypropylene material is solved, and the effect of low shrinkage rate and high dimensional stability is achieved.

CN119823481APending Publication Date: 2025-04-15SUZHOU RUNJIA ENGINEER PLASTIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411744287.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The molding shrinkage rate of polypropylene materials is relatively high, making it difficult to meet the dimensional requirements of precision parts and the dimensional instability caused by temperature changes.

Method used

By adding low-shrinkage modifiers, tougheners, modified whiskers and other components during the preparation of polypropylene, the crystallization and formation of the skeleton are hindered, and its shrinkage performance is reduced.

Benefits of technology

The low shrinkage rate of polypropylene material is achieved, its dimensional stability is improved, and the dimensional requirements of precision components are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163281750000091
    Figure BDA0005163281750000091
Patent Text Reader

Abstract

The invention provides an anti-shrinkage polypropylene material, which is prepared from the following raw materials in parts by weight: 90 to 100 parts of polypropylene, 8 to 12 parts of low-shrinkage modifier A, 10 to 15 parts of low-shrinkage modifier B, 1 to 3 parts of toughening agent, 0.5 to 1.5 parts of compatilizer, 15 to 35 parts of whisker, 5 to 10 parts of dimethyl alkyl chlorosilane and 1 to 5 parts of dispersing agent. Under the synergistic effect of the low-shrinkage modifier, the flexibilizer, the modified whisker and other components, the shrinkage performance of polypropylene is reduced, and the polypropylene material with excellent shrinkage resistance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polypropylene material preparation, and specifically relates to a method for preparing an anti-shrinkage polypropylene material. Background Art

[0002] Polypropylene (PP) is a commonly used thermoplastic with excellent mechanical properties, chemical stability and processing properties. Polypropylene is widely used in many fields, including packaging, automobiles, construction, home appliances, medical treatment, etc.

[0003] The molding shrinkage rate refers to the size difference between the injection molded product and the mold cavity after the material is injected. For those used to manufacture gap-free, high-quality assembly requirements for automobile bumpers, instrument panels, sub-instrument panels, tool box covers, and other parts with precise assembly and small assembly dimensional tolerances, the control of molding shrinkage rate is particularly important.

[0004] There are many factors that affect the shrinkage rate, including the type of plastic (or the structure of the plastic itself), mold structure, mold gate position and molding process conditions. Among them, from the material point of view, the structure of the plastic itself is the main influencing factor. Polypropylene is a semi-crystalline resin, and its molding shrinkage rate is generally 1.4% to 2.6%; it is much higher than the molding shrinkage rate of amorphous materials such as acrylonitrile-butadiene-styrene terpolymer (ABS), polystyrene (PS), and polycarbonate (PC), which are 0.4% to 0.8%; and it has the disadvantages of poor dimensional stability and large linear expansion coefficient, which makes it difficult to meet the dimensional requirements of precision parts and the dimensional instability caused by temperature changes. From the current research, it is difficult to significantly control or reduce the shrinkage rate of polypropylene by relying on a single component, and even if it is achieved, it is at the expense of other properties. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a shrinkage-resistant polypropylene material. In the process of preparing polypropylene, low shrinkage modifiers, toughening agents, modified whiskers and other components are added to reduce the shrinkage performance of polypropylene by hindering crystallization, forming a skeleton and the like, thereby obtaining a polypropylene material with excellent shrinkage resistance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A shrinkage-resistant polypropylene material, the raw materials of which include the following components in parts by weight: 90-100 parts of polypropylene, 8-12 parts of low shrinkage modifier A, 10-15 parts of low shrinkage modifier B, 1-3 parts of toughening agent, 0.5-1.5 parts of compatibilizer, 15-35 parts of whisker, 5-10 parts of dimethyl hydrocarbyl chlorosilane and 1-5 parts of dispersant.

[0008] Furthermore, the polypropylene is homopolymer polypropylene or copolymer polypropylene; the melt flow rate of the polypropylene is 10-15 g / 10 min at 230° C. and 2.16 kg.

[0009] Furthermore, the low shrinkage modifier A is obtained by coating attapulgite with mesoporous silica; and the low shrinkage modifier B is obtained by coating barium sulfate with flaky talc.

[0010] Furthermore, the toughening agent is a mixture of propylene POE and vinyl POE in a mass ratio of 1:2-3.

[0011] Furthermore, the propylene-based POE is a propylene-butene or propylene-ethylene copolymer, and the melt mass flow rate is 3-7 g / 10 min; the vinyl POE is an ethylene-octene copolymer, and the melt mass flow rate is 8-12 g / 10 min.

[0012] Furthermore, the whiskers are nano magnesium hydroxide or basic magnesium sulfate whiskers.

[0013] Furthermore, the compatibilizer is maleic anhydride grafted polypropylene or maleic anhydride grafted polyethylene, and the grafting rate is 0.9-1.15%; the dispersant is vinyl bisstearamide or tristearic acid glyceryl ester.

[0014] The method for preparing the above-mentioned shrinkage-resistant polypropylene material comprises the following steps:

[0015] S1: preparing low shrinkage modifier A and low shrinkage modifier B;

[0016] S2: 90-100 parts of polypropylene, 8-12 parts of low shrinkage modifier A, 10-15 parts of low shrinkage modifier B, 1-5 parts of dispersant, 15-35 parts of whiskers, and 5-10 parts of dimethyl alkyl chlorosilane are mixed to obtain a first premix; then 1-3 parts of toughening agent and 0.5-1.5 parts of compatibilizer are added thereto, and the mixture is placed in a mixer and mixed evenly to obtain a mixed material; wherein the temperature of the mixer is 60-70°C, the speed of the mixer is 120-140r / min, and the mixing is evenly performed to obtain a second premix;

[0017] S3: Add the second premix in step S2 to a twin-screw extruder for four-stage extrusion, the extrusion temperature of the extrusion equipment is 200-225°C, wherein the first zone is 200-205°C, the second zone is 205-210°C, the third zone is 210-220°C, and the fourth zone is 220-225°C; the die head is 220°C, the screw speed is 450-650rpm, the screw aspect ratio is 35:1, and the feed rate is 600-1000kg / h. A low shrinkage polypropylene composition is obtained.

[0018] Furthermore, the process of preparing the low shrinkage modifier A in step S1 is: taking attapulgite and placing it at a temperature of 350-450°C for 5-10min for use; taking the calcined attapulgite and dispersing it in an ethanol solution, the solid-liquid ratio of attapulgite and ethanol solution is 1g:5-10ml, stirring at a temperature of 65-85°C for 45-65min to obtain a dispersion; then adding 4-7% ammonia water to the dispersion and stirring for 20-30min, and then adding 6-10% tetraethyl orthosilicate dropwise to the dispersion; raising the temperature to 60-70°C, stirring the reaction for 1-3h, filtering the precipitate and washing, to obtain a low shrinkage modifier A.

[0019] Furthermore, the process of preparing the low shrinkage modifier B in step S1 is: mixing flaky talc and 1-3 mol / L barium sulfate solution according to a solid-liquid ratio of 1 g: 1.3-1.6 ml, stirring the reaction at a temperature of 60-80°C for 25-35 minutes, and then ultrasonically treating at 1000-1200W for 5-10 minutes to obtain the low shrinkage modifier B.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0021] 1. The present invention uses tetraethyl orthosilicate, ammonia water and attapulgite to prepare a mesoporous silica-coated attapulgite low shrinkage modifier A. The mesoporous silica plays a role similar to that of a steel skeleton. At the same time, the porous void structure of the attapulgite generates steric hindrance in the subsequent polypropylene crystallization process, hinders the crystallization of the polypropylene material, refines the polypropylene unit cell, reduces the shrinkage rate, and improves the dimensional stability.

[0022] 2. The present invention uses flaky talc powder coated with barium sulfate to obtain a low shrinkage modifier B, and utilizes the flaky talc powder to be orderly arranged in the flow direction of the polypropylene melt. At the same time, barium sulfate serves as a strong polar particle to increase the barrier performance and play a role as a nucleating agent, thereby improving the rigidity and shrinkage of the polypropylene material.

[0023] 3. The present invention uses polypropylene, low shrinkage modifier A, low shrinkage modifier B, toughening agent, whisker and dimethyl hydrocarbyl chlorosilane to form a bridge through the hydroxyl groups on the silane molecules with the whisker surface, low shrinkage modifier A, low shrinkage modifier B and polypropylene, and the molecular chains are entangled and bonded, which not only improves the binding force, but also inhibits the shrinkage effect, and further improves the anti-shrinkage performance of polypropylene; its shrinkage rate can reach 0.15%. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The raw materials used in the present invention are as follows:

[0026] Attapulgite comes from Hubei Wande Chemical Co., Ltd. with item number WD1473; ethyl orthosilicate comes from Wuhan Jiyesheng Chemical Co., Ltd. with item number 4069; flaky talc comes from Shanghai Yuanye Biotechnology Co., Ltd. with item number S30618; dimethyl alkylchlorosilane comes from Shanghai Yuanye Biotechnology Co., Ltd. with item number S50512; homopolypropylene comes from Dongguan Jinshixiang Plastic Raw Materials Co., Ltd. with item number 519A; copolymer polypropylene comes from Dongguan Jinshixiang Plastic Raw Materials Co., Ltd. with item number 358A; nano magnesium hydroxide and basic magnesium sulfate whiskers come from Shanghai Sijun Machinery Equipment Co., Ltd.; vinyl bisstearamide comes from Nantong Runfeng Petrochemical Co., Ltd. with item number 5102; tristearic acid glycerol comes from Shanghai Yuanye Biotechnology Co., Ltd. with item number S48334; propylene-butene copolymer, propylene-ethylene copolymer, and ethylene-octene copolymer come from Hubei Xinhongli Chemical Co., Ltd.; maleic anhydride grafted polypropylene comes from Nanjing Bermuda Biotechnology Co., Ltd. with item number 5104.

[0027] Example 1

[0028] This embodiment provides a method for preparing an anti-shrinkage polypropylene material, comprising the following steps:

[0029] S1: Take attapulgite and place it at a temperature of 350℃ for 5 minutes for use; take the calcined attapulgite and disperse it in an ethanol solution according to a solid-liquid ratio of 1g:5ml, stir it at a temperature of 65℃ and a speed of 500r / min for 45min to obtain a dispersion; then add ammonia water accounting for 4% of the dispersion and stir it at a speed of 600r / min for 20min, then add ethyl orthosilicate accounting for 6% of the dispersion drop by drop at a speed of 1 drop / s; raise the temperature to 75℃, stir and react at a speed of 600r / min for 1h, filter the precipitate and wash it to obtain a low shrinkage modifier A;

[0030] The flaky talc powder and 1 mol / L barium sulfate solution were mixed at a solid-liquid ratio of 1 g:1.3 ml, stirred at a speed of 350 r / min for 25 min at a temperature of 60°C, and then ultrasonically treated at 1000 W for 5 min to obtain a low shrinkage modifier B;

[0031] S2: 90g of polypropylene, 8g of low shrinkage modifier A, 10g of low shrinkage modifier B, 1g of dispersant, 15g of whiskers, and 5g of dimethylalkylchlorosilane are mixed to obtain a first premix; wherein the polypropylene is homopolymer polypropylene, and the melt flow rate is 10g / 10min at 230°C and 2.16kg; the whiskers are nano magnesium hydroxide; and the dispersant is vinyl bisstearamide;

[0032] Then, 1g of toughening agent and 0.5g of compatibilizer are added thereto, and the mixture is placed in a mixer and mixed evenly to obtain a mixed material; the toughening agent is a mixture of propylene-butene copolymer (melt mass flow rate is 3g / 10min) and ethylene-octene copolymer (melt mass flow rate is 8g / 10min) in a mass ratio of 1:2; the compatibilizer is maleic anhydride grafted polypropylene, and the grafting rate is 0.9%; wherein the temperature of the mixer is 60°C, the speed of the mixer is 120r / min, and the second premix is ​​mixed evenly to obtain the second premix;

[0033] S3: adding the second premix in step S2 to a twin-screw extruder for four-stage extrusion, the extrusion temperature of the extrusion equipment is 200-220°C, wherein the first zone is 200°C, the second zone is 205°C, the third zone is 210°C, and the fourth zone is 220°C; the die is 220°C, the screw speed is 450rpm, the screw aspect ratio is 35:1, and the feed rate is 600kg / h; and a low shrinkage polypropylene composition is obtained.

[0034] Example 2

[0035] This embodiment provides a method for preparing an anti-shrinkage polypropylene material, comprising the following steps:

[0036] S1: Take attapulgite and place it at a temperature of 450℃ for 10min for use; take the calcined attapulgite and disperse it in an ethanol solution according to a solid-liquid ratio of 1g:10ml, stir the attapulgite and ethanol solution at a temperature of 85℃ at a rate of 400r / min for 65min to obtain a dispersion; then add ammonia water accounting for 7% of the dispersion and stir at a rate of 600r / min for 30min, then add 10% of tetraethyl orthosilicate dropwise at a rate of 5 drops / s; raise the temperature to 85℃, stir the reaction at a rate of 550r / min for 3h, filter the precipitate and wash it to obtain a low shrinkage modifier A;

[0037] The flaky talc powder and 3 mol / L barium sulfate solution were mixed at a solid-liquid ratio of 1 g:1.6 ml, stirred at a speed of 550 r / min for 35 min at a temperature of 80°C, and then ultrasonically treated at 1200 W for 10 min to obtain a low shrinkage modifier B;

[0038] S2: 100g of polypropylene, 12g of low shrinkage modifier A, 15g of low shrinkage modifier B, 5g of dispersant, 35g of whiskers, and 10g of dimethylalkylchlorosilane are mixed to obtain a first premix; wherein the polypropylene is copolymerized polypropylene, and the melt flow rate is 15g / 10min at 230°C and 2.16kg; the whiskers are basic magnesium sulfate whiskers; and the dispersant is tristearate glyceryl;

[0039] Then, 3g of toughening agent and 1.5g of compatibilizer were added thereto, and the mixture was placed in a mixer and mixed evenly to obtain a mixed material; the toughening agent was a propylene-ethylene copolymer (melt mass flow rate was 7g / 10min) and an ethylene-octene copolymer (melt mass flow rate was 12g / 10min) in a mass ratio of 1:3; the compatibilizer was maleic anhydride grafted polyethylene, and the grafting rate was 1.15%; wherein the temperature of the mixer was 70°C, the speed of the mixer was 140r / min, and the second premix was mixed evenly to obtain the second premix;

[0040] S3: Add the second premix of step S2 into a twin-screw extruder for four-stage extrusion. The extrusion temperature of the extrusion equipment is 205-225°C, wherein the first zone is 205°C, the second zone is 210°C, the third zone is 220°C, and the fourth zone is 225°C; the die is 220°C, the screw speed is 650rpm, the screw aspect ratio is 35:1, and the feed rate is 1000kg / h to obtain a low shrinkage polypropylene composition.

[0041] Example 3

[0042] This embodiment provides a method for preparing an anti-shrinkage polypropylene material, comprising the following steps:

[0043] S1: Take attapulgite and place it at a temperature of 420℃ for 8 minutes for use; take the calcined attapulgite and disperse it in an ethanol solution according to a solid-liquid ratio of 1g:7ml, stir it at a temperature of 80℃ and a speed of 600r / min for 55min to obtain a dispersion; then add ammonia water accounting for 6% of the dispersion and stir it at a speed of 500r / min for 25min, then add ethyl orthosilicate accounting for 8% of the dispersion dropwise at a speed of 3 drops / s; raise the temperature to 80℃, stir and react at a speed of 600r / min for 2.5h, filter the precipitate and wash it to obtain a low shrinkage modifier A;

[0044] The flaky talc powder and 2.5 mol / L barium sulfate solution were mixed at a solid-liquid ratio of 1 g:1.45 ml, stirred at 400 r / min for 30 min at 75°C, and then ultrasonically treated at 1150 W for 8 min to obtain a low shrinkage modifier B;

[0045] S2: 95g of polypropylene, 10g of low shrinkage modifier A, 13g of low shrinkage modifier B, 3g of dispersant, 25g of whiskers, and 8g of dimethylalkylchlorosilane are mixed to obtain a first premix; wherein the polypropylene is homopolymer polypropylene, and the melt flow rate is 12g / 10min at 230°C and 2.16kg; the whiskers are nano basic magnesium sulfate whiskers; and the dispersant is vinyl bisstearamide;

[0046] Then, 2g of toughening agent and 1.3g of compatibilizer were added thereto, and the mixture was placed in a mixer and mixed evenly to obtain a mixed material; the toughening agent was a propylene-butene copolymer (melt mass flow rate was 5g / 10min) and an ethylene-octene copolymer (melt mass flow rate was 10g / 10min) in a mass ratio of 1:2.5; the compatibilizer was maleic anhydride grafted polypropylene, and the grafting rate was 1.05%; wherein the temperature of the mixer was 65°C, the speed of the mixer was 130r / min, and the second premix was mixed evenly to obtain the second premix;

[0047] S3: Add the second premix in step S2 to a twin-screw extruder for four-stage extrusion. The extrusion temperature of the extrusion equipment is 203-223°C, wherein the first zone is 203°C, the second zone is 208°C, the third zone is 215°C, and the fourth zone is 223°C; the die is 220°C, the screw speed is 600rpm, the screw aspect ratio is 35:1, and the feed rate is 850kg / h to obtain a low shrinkage polypropylene composition.

[0048] Comparative Example 1

[0049] The difference between this comparative example and Example 1 is that the low shrinkage modifier A is missing in step S2, and the other steps are the same.

[0050] Comparative Example 2

[0051] The difference between this comparative example and Example 1 is that the low shrinkage modifier B is missing in step S2, and the other steps are the same.

[0052] Comparative Example 3

[0053] The difference between this comparative example and Example 1 is that whiskers are missing in step S2, and the other steps are the same.

[0054] Comparative Example 4

[0055] The difference between this comparative example and Example 1 is that dimethyl hydrocarbyl chlorosilane is missing in step S2, and the other steps are the same.

[0056] Comparative Example 5

[0057] The difference between this comparative example and Example 1 is that there is no toughening agent in step S2, and the other steps are the same.

[0058] Performance Testing:

[0059] Tensile strength: tested according to ISO 527-2-2016 standard, the tensile speed is 50mm / min; Izod notch impact strength: tested according to ISO180-2000 standard; Molding shrinkage: tested according to GB / T17037.4-2003 standard, the sample is a small square piece of 60×60×2mm, the test results are shown in Table 1.

[0060] Table 1

[0061]

[0062] It can be seen from the above performance test results that Examples 1-3 have excellent performance in terms of tensile strength, Izod notched impact strength, molding shrinkage, etc. In particular, the comprehensive performance of Example 3 is the most outstanding. However, since Comparative Examples 1-5 do not adopt the necessary technical solutions, their corresponding performance tests are significantly worse than those of the Examples. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.

[0063] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A shrinkage-resistant polypropylene material, characterized in that: The raw materials include the following components in parts by weight: 90-100 parts of polypropylene, 8-12 parts of low shrinkage modifier A, 10-15 parts of low shrinkage modifier B, 1-3 parts of toughening agent, 0.5-1.5 parts of compatibilizer, 15-35 parts of whisker, 5-10 parts of dimethyl hydrocarbyl chlorosilane and 1-5 parts of dispersant.

2. The shrinkage-resistant polypropylene material according to claim 1, characterized in that: The polypropylene is homopolymer polypropylene or copolymer polypropylene; the melt flow rate of the polypropylene is 10-15 g / 10 min at 230° C. and 2.16 kg.

3. The shrinkage-resistant polypropylene material according to claim 1, characterized in that: The low shrinkage modifier A is obtained by coating attapulgite with mesoporous silica; and the low shrinkage modifier B is obtained by coating barium sulfate with flaky talc.

4. The shrinkage-resistant polypropylene material according to claim 1, characterized in that: The toughening agent is a mixture of propylene POE and vinyl POE in a mass ratio of 1:2-3.

5. The shrinkage-resistant polypropylene material according to claim 4, characterized in that: The propylene-based POE is a propylene-butene or propylene-ethylene copolymer, and the melt mass flow rate is 3-7 g / 10 min; the vinyl-based POE is an ethylene-octene copolymer, and the melt mass flow rate is 8-12 g / 10 min.

6. The shrinkage-resistant polypropylene material according to claim 1, characterized in that: The whiskers are modified nano magnesium hydroxide or basic magnesium sulfate whiskers.

7. The shrinkage-resistant polypropylene material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene or maleic anhydride grafted polyethylene, and the grafting rate is 0.9-1.15%; the dispersant is vinyl bis stearamide or tristearic acid glyceryl ester.

8. A method for preparing a shrinkage-resistant polypropylene material, characterized in that: The steps include: S1: preparing low shrinkage modifier A and low shrinkage modifier B; S2: 90-100 parts of polypropylene, 8-12 parts of low shrinkage modifier A, 10-15 parts of low shrinkage modifier B, 1-5 parts of dispersant, 15-35 parts of whiskers and 5-10 parts of dimethyl hydrocarbyl chlorosilane are mixed to obtain a first premix; then 1-3 parts of toughening agent and 0.5-1.5 parts of compatibilizer are added thereto, and the mixture is placed in a mixer and mixed evenly to obtain a mixed material; wherein the temperature of the mixer is 60-70° C., the speed of the mixer is 120-140 r / min, and the mixing is evenly performed to obtain a second premix; S3: Add the second premix in step S2 to a twin-screw extruder for four-stage extrusion, the extrusion temperature of the extrusion equipment is 200-225°C, wherein the first zone is 200-205°C, the second zone is 205-210°C, the third zone is 210-220°C, and the fourth zone is 220-225°C; the die head is 220°C, the screw speed is 450-650rpm, the screw aspect ratio is 35:1, and the feed rate is 600-1000kg / h. A low shrinkage polypropylene composition is obtained.

9. The method for preparing a shrinkage-resistant polypropylene material according to claim 8, characterized in that: The process of preparing the low shrinkage modifier A in step S1 is as follows: taking attapulgite and calcining it at a temperature of 350-450°C for 5-10min for standby use; taking the calcined attapulgite and dispersing it in an ethanol solution, the solid-liquid ratio of attapulgite to ethanol solution is 1g:5-10ml, stirring at a temperature of 65-85°C for 45-65min to obtain a dispersion; then adding 4-7% ammonia water to the dispersion and stirring for 20-30min, and then adding 6-10% ethyl orthosilicate dropwise to the dispersion; raising the temperature to 60-70°C, stirring the reaction for 1-3h, filtering the precipitate and washing, to obtain a low shrinkage modifier A.

10. The method for preparing a shrinkage-resistant polypropylene material according to claim 9, characterized in that: The process of preparing the low shrinkage modifier B in step S1 is as follows: flaky talc and 1-3 mol / L barium sulfate solution are mixed according to a solid-liquid ratio of 1 g: 1.3-1.6 ml, stirred for reaction at a temperature of 60-80° C. for 25-35 min, and then ultrasonically treated at 1000-1200 W for 5-10 min to obtain the low shrinkage modifier B.